Rancang Bangun Sistem Pilkades Menggunakan Teknologi Smart Card Sebagai Kartu Pemilih - Indra Permana, I Putu; Putra, I Ketut Gede Darma; Sasmita, I Gusti Made Arya (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 2 Agustus 2016, 2016)
Village Head Election (Pilkades) is an inseparable process in the State of Indonesia as a democracy country. Pilkades today still uses a voting system conventionally, using media in form of paper to conduct the electoral process. Implementation of the conventional voting system has many weaknesses, such as the time to count the voting results are relatively longer and it still uses manual calculation. The advance development in recent information technology can be used to support the better implementation of the Pilkades voting which expected to be a smart solution that in the future may replace the conventional voting system, for example by electronic voting system (e-voting) which is using smart card technology as a voter card. The system is packaged in the form of apps installed on the computer and a reader/writer tool as a media to read/write on the smart e-voting card. Pilkades system with smart card technology has been successfully executed and in the dashboard apps is shown the number of voting in Pilkades voting results in the form of numbers, percentages (%), graphs and charts.
Keywords: Pemilihan Kepada Desa (Pilkades); E-Voting; Smart Card; Reader/Writer Tool; Teknologi Informasi